Alleviating Poverty in Nigeria: Keynesian vs Monetary Theory of Poverty - Maku, Olukayode Emmanuel; Tella, Afeez Taiwo; Fagbohun, Akinola Christopher (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2020)
This study comparatively investigates the impacts of fiscal and monetary policies on poverty in Nigeria from 1986 to 2018. Using the Ordinary Least Square and Standardized or Beta Coefficient approach, we found that the Nigerian political system plays a vital role on a large number of its citizens living in extreme poverty. Other factors identified as the likely causes of poverty are insurgencies, terrorism, and low productivity among others. Also, monetary policy is more important in alleviating poverty than the fiscal policy which favored the monetary school arguments. Specifically, monetary measures like exchange rate and interest rate are more significant in alleviating poverty far more than inflation rate while fiscal measures proxy with government recurrent expenditure plays a more vital role in alleviating poverty in Nigeria than others like government capital expenditure and government recurrent expenditure. The study recommended that in the case of monetary measures, there is a need for Government through the Central Bank of Nigeria, to shift their attention towards key monetary policy measures like interest rate and exchange rate compare to other monetary measures.